Joint channel and Doppler estimation for multicarrier underwater communications - Kibangou, A Y; Siclet, C; Ros, L (2010 IEEE International Conference on Acoustics, Speech and Signal Processing, 2010)
Underwater wireless communications are subject to multipath propagation and Doppler effects. In the receiver side, it is necessary to estimate both Doppler and channel parameters in order to compensate for their effects in the transmitted signal. In this paper, in the OFDM (Orthogonal Frequency Division Multiplexing) context, we derive a new estimation scheme based on the resolution of two harmonic retrieval problems. Unlike standard methods, data resampling and estimation of residual carrier frequency offset are avoided. The efficiency of the proposed scheme is evaluated by means of simulations.